Investigating the usability pattern and constraints of pocket parks in Kuala Lumpur, Malaysia - Balai Kerishnan, Praveena; Maruthaveeran, Sreetheran; Maulan, Suhardi (Elsevier, 2020)
This study aims to provide an overview of the pocket parks in the city centre of Kuala Lumpur while identifying the characteristics of the pocket parks associated with the visitation and usage. This study also intends to identify the constraints that limit the use of pocket parks according to Malaysia context. A survey conducted among N=363 respondents consisting of pocket parks users and non-users are presented and discussed. Overall the pocket parks in Kuala Lumpur are used by the respondents to rest and reduce stress. This study concluded that slightly more women use the pocket parks than men and lack of time was the main constraint that limited the use of pocket parks in Kuala Lumpur. A higher majority of respondents also cited their willingness to use the pocket parks more often if changes were implemented to make the pocket park safer and more facilities were provided. The findings contribute to an understanding of the factors that influence the usability pattern and constraints that limit the usage of pocket parks in Kuala Lumpur. Further, a well-managed and maintained pocket park would create opportunities for all segments of the urban community to use the parks more often.